The factorial structure of some physical measurements as an indicator for the selection of judo players in the Kingdom of Saudi Arabia - Masoudi, Maher (Journal of Physical Education, 2023)
Objectives: The general objective of this study is to employ the factorial Structure of some physical measurements as an indicator for the selection of judo players. Methods: The study used the descriptive approach using the survey method, the sample size was (30) judo players from the youth category, representing clubs (Al-Shabab, Uhud, and Al-Ansar). To achieve the goal of the study, the researcher relied on some physical measurements such as measuring lengths, circumferences, widths, depths, body surface area, in addition to body composition measurements The study measurements were conducted in January 2023 AD in the Laboratory of the Department of Physical Education and Sports Sciences, and in the outdoor courts at Taibah University, KSA Results: The results of the study indicated the emergence of four basic factors in the physical measurements of judo players, and they can be used as an indicator for selecting judo players, which are as follows: (Forearm circumference / left, total length, thigh circumference / left, fat percentage). Recommendations; The study recommends the necessity of paying attention to the physical determinants of judo players highlighted in this study. This factors can be utilized As a scientific basis for the selection of judo players in the Kingdom of Saudi Arabia, and in organizing and directing training programs for judo players